Bilateral Vestibular Dysfunction Associated With Chronic Exposure to Military Jet Propellant Type-Eight Jet Fuel - Fife, Terry D.; Robb, Michael J. A.; Steenerson, Kristen K.; Saha, Kamala C. (Frontiers in Neurology, 2018)
We describe three patients diagnosed with bilateral vestibular dysfunction associated with JP-8 fuel exposure. Chronic exposure to aromatic and aliphatic hydrocarbons, which are the main constituents of JP-8 military aircraft jet fuel, occurred over three to five years’ duration while working on or near the flight line. Exposure to toxic hydrocarbons was substantiated by the presence of JP-8 metabolite n-hexane in the blood of one of the cases. The presenting symptoms were dizziness, headache, fatigue, and imbalance. Quantitative rotational chair testing confirmed bilateral vestibular dysfunction in all three patients. Vestibular function improved over time once the exposure was removed. Bilateral vestibular dysfunction has been associated with hydrocarbon exposure in humans, but only recently has emphasis been placed specifically on the detrimental effects of JP-8 jet fuel and its numerous hydrocarbon constituents. Data is limited on the mechanism of JP-8 induced vestibular dysfunction or ototoxicity. Early recognition of JP-8 toxicity risk, cessation of exposure and customized vestibular therapy offer the best chance for improved balance. Bilateral vestibular impairment is under-recognized in those chronically exposed to all forms of jet fuel.